THE EFFECTIVENESS OF COOPERATIVE LEARNING TO IMPROVE STUDENTS SPEAKING COMMUNICATIVE SKILLS AT GRADE VII OF SMP PGRI 174 CIKUPA TANGERANG - Rika Yusniah; Reynita Andriana (Sekolah Tinggi Keguruan dan Ilmu Pendidikan Banten, 2012)
The technique of collecting data was by using a test. After the data of the effectiveness of cooperative learning and to improve students speaking communicative skills were collected, the data were statistically computed to find out the correlation between the two varibales. The writer analyzes the data based on the effectiveness of cooperative learning to improve students speaking communicative skills. This data is analyzed by using correlation product moment. The value of correlation coefficient obtained is 0,544, while the criteria of the correlation between 0,40 to 0,70 are considered moderate. It means that the level of relationship of the correlation coefficient of the two variables is moderate. In this research the variable Y is influenced too high by the variable X and the other way the varble is also influenced too high by the variable Y. For the contribution variable X to Variable Y, the writer get influence 29,60 % applying the effectiveness of cooperative learning to improve students speaking communicative skills and 70,4 % left is influenced by other factor, it means that the effectiveness of cooperative learning to improve students speaking communicative skills at grade VII of SMP PGRI 174 Cikupa Tangerang has quite influence.